The influencing machine : Brooke Gladstone on the media - Gladstone, Brooke; Neufeld, Josh.; Jones, Randy, 1950-; Jones, Susann (New York : W.W. Norton, 2011)
The cohost of NPR's'On the Media' narrates, in cartoon form, two millennia of history of the influence of the media on the populace, from newspapers in Caesar's Rome to the penny press of the American Revolution to today.
In the beginning -- The American exception -- Existential angst -- Canis journalisticus -- Birds on a wire -- News you can't use -- The great refusal -- Bias -- War -- Objectivity -- Disclosure -- The matrix in me -- The influencing machines -- Um, panic? -- I, robot -- I media.
Includes bibliographical references (p. 163-170).
Keywords: Gladstone, Brooke -- Comic books, strips, etc; Journalism -- Comic books, strips, etc; Broadcast journalism -- Comic books, strips, etc; Graphic novels